The role of the E3 ligase Not4 in cotranslational quality control - Panasenko, Olesya O. (Frontiers in Genetics, 2014)
Cotranslational quality control (QC) is the mechanism by which the cell checks the integrity of newly synthesized proteins and mRNAs. In the event of mistakes these molecules are degraded. The Ccr4-Not complex has been proposed to play a role in this process. It contains both deadenylation and ubiquitination activities, thus it may target both aberrant proteins and mRNAs. Deadenylation is the first step in mRNA degradation. In yeast it is performed by the Ccr4 subunit of the Ccr4-Not complex. Another complex subunit, namely Not4, is a RING E3 ligase and it provides the ubiquitination activity of the complex. It was found associated with translating ribosomes. Thus, it has been suggested that Not4 is involved in ribosome-associated ubiquitination and degradation of aberrant peptides. However, several other E3 ligases have been associated with peptide ubiquitination on the ribosome and the relevance of Not4 in this process remains unclear. In this review we summarize the recent data and suggest a role for Not4 in cotranslational protein QC.